Anti-Oxidative Effect of Weak Alkaline Reduced Water in RAW 264.7 Murine Macrophage Cells - Thuy Thi Trinh (MDPI AG, 2021)
Excessive oxidative stress (OS) is a common cause of various diseases such as cancer, diabetes, and obesity; thus, an anti-oxidative solution is essential for the improvement of human health. Increasing evidence suggests that alkaline reduced water (ARW), especially between pH 9.5–10.0, has antioxidant capacity; however, relatively few studies have reported the effect of weak ARW at pH 8.5 on OS, especially in vitro. This study was conducted to evaluate the anti-oxidative efficacy of weak ARW with negative oxidation-reduction potential (ORP) and relatively high hydrogen (H2) concentration, as compared to tap water (TW) and ARW at pH 9.5. RAW 264.7 murine macrophage cells, stimulated by hydrogen peroxide (H2O2) and lipopolysaccharide (LPS) to induce OS, were used as a control (Con) and then treated with TW and ARW at pH 8.5 (ARW_8.5) and pH 9.5 (ARW_9.5) at different concentrations (0.1%, 1%, and 10% v/v). Results showed that cell viability was significantly restored after treatment with both ARW_8.5 and ARW_9.5 compared to Con/H2O2 and Con/LPS, while TW treatment did not induce significant changes. Levels of reactive oxygen species (ROS), nitric oxide (NO), Ca2+, catalase, and glutathione peroxide (GPx) showed significant differences in a concentration-dependent manner in ARW_8.5 and ARW_9.5 groups compared to Con/H2O2 and Con/LPS groups. Likewise, the expression of p-p38, p-JNK, and p-ERK was also significantly reduced in the ARW-treated groups, but not in the TW group. In conclusion, ARW_8.5 exhibited anti-oxidative effects through the regulation of the MAPK signaling pathway in RAW 264.7 murine macrophage cells, indicating the health-promoting potential of weak ARW through daily intake.